Ductal Lavage in Women from BRCA1/2 Families: Is There a Future for Ductal Lavage in Women at Increased Genetic Risk of Breast Cancer? - Loud, Jennifer T. (2009)
PURPOSE: Ductal lavage has been used for risk stratification and biomarker development and to identify intermediate endpoints for risk-reducing intervention trials. Little is known about patient characteristics associated with obtaining nipple aspirate fluid (NAF) and adequate cell counts (≥10 cells) in ductal lavage specimens from BRCA mutation carriers. METHODS: We evaluated patient characteristics associated with obtaining NAF and adequate cell counts in ductal lavage specimens from the largest cohort of women from BRCA families yet studied (BRCA1/2 = 146, mutation-negative = 23, untested = 2). Fisher’s exact test was used to evaluate categorical variables; Wilcoxon nonparametric test was used to evaluate continuous variables associated with NAF or ductal lavage cell count adequacy. Logistic regression was used to identify independent correlates of NAF and ductal lavage cell count adequacy. RESULTS: From 171 women, 45 (26%) women had NAF and 70 (41%) women had ductal lavage samples with ≥10 cells. Postmenopausal women with intact ovaries compared with premenopausal women [odds ratio (OR), 4.8; P = 0.03] and women without a prior breast cancer history (OR, 5.2; P = 0.04) had an increased likelihood of yielding NAF. Having breast-fed (OR, 3.4; P = 0.001), the presence of NAF before ductal lavage (OR, 3.2; P = 0.003), and being premenopausal (OR, 3.0; P = 0.003) increased the likelihood of ductal lavage cell count adequacy. In known BRCA1/2 mutation carriers, only breast-feeding (OR, 2.5; P = 0.01) and the presence of NAF (OR, 3.0; P = 0.01) were independent correlates of ductal lavage cell count adequacy. CONCLUSIONS: Ductal lavage is unlikely to be useful in breast cancer screening among BRCA1/2 mutation carriers because the procedure fails to yield adequate specimens sufficient for reliable cytologic diagnosis or to support translational research activities.